Incidental Diagnosis of Prostate Cancer by 18F-FDG PET-CT Imaging in a Patient During Post-operative Evaluation for Cecal Cancer (Bangladesh Journal of Nuclear Medicine, 2023)
Incidental high fluorine-18 FDG (fluorodeoxyglucose) uptake in well-differentiated prostate cancer is rare. We reported the case of a 75-year-old man who underwent a whole-body FDG PET-CT (positron emission tomography with computed tomography) scan for post-operative evaluation of caecal cancer and demonstrated no evidence of recurrence. However, a focal hypermetabolic lesion was detected in the right lateral lobe of the prostate. The patient’s prostatic biopsy from the right lobe revealed well-differentiated adenocarcinoma with a Gleason score of six and a raised serum PSA level. Incidental, focally intense FDG uptake in the prostate gland should be considered for further investigations to confirm the presence of prostate cancer.Bangladesh J. Nuclear Med. 26(1): 51-53, 2023